1998
DOI: 10.1021/jo972260d
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Complex-Catalyzed N-(Cyclo)alkylation of Aromatic Amines with Diols. Selective Synthesis of N-(ω-Hydroxyalkyl)anilines of Type PhNH(CH2)nOH and of Some Bioactive Arylpiperazines

Abstract: A new class of well-defined neutral mono-, and dicationic ruthenium(II) complexes containing a neutral terdentate donor system [C 5 H 3 N(CH 2 E) 2-2,6] (E) PPh 2 (PNP) or NMe 2 (NN′N)) has been found effective as catalyst precursor in N-(cyclo)alkylation reactions of aromatic amines with diols Y(CH 2 CH 2 OH) 2 (Y) CH 2 , NR). With these catalysts, N-phenylpiperidine is synthesized from aniline and 1,5-pentanediol in 85% yield (at 180°C for 24 h in 1,4-dioxane). With neutral RuCl 2 (NN′N)-(PPh 3) as a catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 60 publications
1
76
0
2
Order By: Relevance
“…[61] This result can be related to the recent reactivity observed by Milstein and co-workers for analogous Ru complexes. [55] Gibson et al independently reported the formation of some Ru complexes with 12 tBu in 2004 (Scheme 13), [62] simultaneously with the first application of this catalyst system for the acceptorless dehydrogenation of alcohols by Milstein and co-workers.…”
Section: Other Chemistry With Rutheniumsupporting
confidence: 66%
“…[61] This result can be related to the recent reactivity observed by Milstein and co-workers for analogous Ru complexes. [55] Gibson et al independently reported the formation of some Ru complexes with 12 tBu in 2004 (Scheme 13), [62] simultaneously with the first application of this catalyst system for the acceptorless dehydrogenation of alcohols by Milstein and co-workers.…”
Section: Other Chemistry With Rutheniumsupporting
confidence: 66%
“…No peaks for any residual un-bounded dendritic phosphine groups were observed, suggesting high efficiency of metal loading on these organophosphine dendrimers. The spectrum of 7 resembled that of the corresponding PPh 3 complex [Ru(NN%N)PPh 3 Cl 2 ], which showed a signal at 37 ppm [4]. The coordination chemical shifts of 7 and 8 are 43.1 and 10.3 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study we found that mononuclear Ru(II) complexes, [Ru(NN%N)(PPh 3 )Cl 2 ] (1, NN%N = 2,6-bis[(dimethylamino)methyl]pyridine), are interesting catalysts for the cycloalkylation of aromatic amines with alcohols to give piperazines and piperidines [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] Dieses Resultat ähnelt den Ergebnissen von Milstein und Mitarbeitern für analoge Rutheniumkomplexe. [55] Gibson et al berichteten im Jahr 2004 davon unabhängig über die Bildung einiger Rutheniumkomplexe mit 12 tBu (Schema 13) [62] und deren erstmalige Anwendung bei der akzeptorfreien Dehydrierung von Alkoholen, was praktisch …”
Section: Weitere Reaktionen Mit Rutheniumkomplexenunclassified